1997
DOI: 10.1182/blood.v90.3.1217.1217_1217_1225
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Wilms' Tumor Gene (wt1) mRNA in Acute Myeloid Leukemias Are Associated With a Worse Long-Term Outcome

Abstract: The tumor suppressor gene wt1 (Wilms' tumor gene) encodes for a zinc finger DNA-binding protein with predominantly transcription repressing properties. Because wt1 has been shown to be expressed in the vast majority of patients with acute myeloid leukemias (AML), we investigated the relevance of wt-1 mRNA expression regarding prognosis and possible prediction of relapse during follow-up. Totally bone marrow-derived blasts of 139 AML patients (129 newly diagnosed AML patients, 22 AML patients again in first rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
2
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 28 publications
3
101
2
5
Order By: Relevance
“…(Inoue et al, 1996(Inoue et al, , 1997. Several studies (Brieger et al, 1994;Schmid et al, 1997) using a qualitative assay for WT1 in AML found no correlation between WT1 expression at diagnosis and achievement of CR, whereas Bergmann et al (1997) have shown a tendency towards a higher CR rate in patients with low-level expression of WT1 mRNA using a semiquantitative technique. However, Inoue et al (1996) showed a clear inverse correlation between high WT1 levels in AL and prognosis in terms of CR, DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…(Inoue et al, 1996(Inoue et al, , 1997. Several studies (Brieger et al, 1994;Schmid et al, 1997) using a qualitative assay for WT1 in AML found no correlation between WT1 expression at diagnosis and achievement of CR, whereas Bergmann et al (1997) have shown a tendency towards a higher CR rate in patients with low-level expression of WT1 mRNA using a semiquantitative technique. However, Inoue et al (1996) showed a clear inverse correlation between high WT1 levels in AL and prognosis in terms of CR, DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies reported an overexpression of WT1 in various hematological malignancies, including AML where WT1 is highly expressed at diagnosis in about 80-90% of cases (1)(2)(3)(4)(5)(6). Moreover, it is now evident that WT1 values correlate with disease status, thus being a good candidate for the evaluation of MRD during and after treatment, especially in the relevant percentage of patients who lack a specific molecular marker of their disease (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The aim of the present study was to explore if the WT1 quantitative expression evaluation may be a useful marker of MRD in patients with AML after reduced-intensity conditioning (RIC)-SCT.…”
mentioning
confidence: 99%
“…Studies investigating the clinical value of WT1 RNA detection produced conflicting results. While few investigators draw a clear correlation between strong WT1 expression at initial diagnosis and poor prognosis (Inoue et al, 1994;Bergmann et al, 1997), others could not confirm these findings (Schmid et al, 1997).…”
mentioning
confidence: 99%